Penggunaan Media Sosial sebagai Sarana Berdakwah - Efendi, Erwan; Raefaldhi, Muhammad; Al Farisi, M. Salman (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this era, the use of social media is increasingly being used by the community, especially among adolescents and adults. However, the use of social media is very widespread. And this depends on the person using it. If social media is used properly, such as as a means of preaching, then this is very good. Therefore, if a preacher wants to spread his message, a preacher must first have a social media account, either Facebook, Twitter, Instagram, TikTok, etc. The use of social media must be in accordance with the teachings of Islamic law. Providing positive things such as preaching, then this can be a reward that is generous in the future. Therefore, to obtain accurate data in this paper, the library method is used by searching, collecting, and analyzing relevant books. Keywords: media, social, da'wah